Penerapan Inovasi Digital dalam Meningkatkan Kualitas Layanan di Kantor Depan (Studi Kasus ValStar Hotel Canggu) - Endrayani Endrayani; Ida Bagus Nyoman Krisna Prawira Yuda (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
This study examines the application of digital innovation in improving service quality in the front office. This study aims to determine what innovation technologies have been implemented in the front office and the extent of their utilization in the check-in, check-out, guest information, complaint handling and payment processes and how the application of digital innovation in the front office department contributes to improving service quality according to the SERVQUAL dimension theory. The method used is the phenomenon method with interviews, observations and document analysis. The results of the study show that the non-cash payment system (QRIS) is scanned on the POS machine (contactless payment), 2. QR codes integrated with the hotel website are available in each guest room, 3. Customer relationship management (CRM) is connected to an AI chatbot. Based on the SERVQUAL dimension analysis, digital innovation has a positive impact on the dimensions of tangibles, reliability, responsiveness and assurance, while the empathy dimension of the hotel management team strives to improve guest needs, because this is a point of influence on service quality. This study contributes to providing an overview for the ValStar Hotel management team in formulating the SERVQUAL dimension theory of service quality.